2009
DOI: 10.1073/pnas.0905724106
|View full text |Cite
|
Sign up to set email alerts
|

TR4 nuclear receptor functions as a fatty acid sensor to modulate CD36 expression and foam cell formation

Abstract: Testicular orphan nuclear receptor 4 (TR4) is an orphan member of the nuclear receptor superfamily with diverse physiological functions. Using TR4 knockout (TR4 ؊/؊ ) mice to study its function in cardiovascular diseases, we found reduced cluster of differentiation (CD)36 expression with reduced foam cell formation in TR4 ؊/؊ mice. Mechanistic dissection suggests that TR4 induces CD36 protein and mRNA expression via a transcriptional regulation. Interestingly, we found this TR4-mediated CD36 transactivation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 44 publications
1
119
0
Order By: Relevance
“…The pSuperior.retro.puro. plasmids containing scramble small hairpin RNA (shRNA) and shRNA targeting TR4 were described in a previous publication [2]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pSuperior.retro.puro. plasmids containing scramble small hairpin RNA (shRNA) and shRNA targeting TR4 were described in a previous publication [2]. …”
Section: Methodsmentioning
confidence: 99%
“…and Tsai et al . found that the polyunsaturated fatty acid metabolites 15-HETE, 13-HODE, and γ-linoleic acid are able to activate TR4 [2, 3]. This suggests that TR4 may be able to function as a fatty acid sensor upon activation via these ligands/activators.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, from those extensive in vivo function studies, Xie et al (2009) discovered that the PUFA metabolites, 15-hydroxyeicosatetraenoic acid (15-HETE) and 13-hydroxyoctadecadienoic acid (13-HODE) as well as rosiglitazone, could function as ligands/activators to transactivate TR4 to a degree similar to PPARg. These unexpected results link these two different NRs and raise some very interesting questions.…”
Section: Introduction: the History Of Cloning/isolation Of Pparg And mentioning
confidence: 99%
“…Several reports have shown that trans-10, cis-12 CLA competitively inhibits effect of PPARγ agonist on PPARγ activity while it rather plays a role as a partial agonist of PPARγ in the absence of PPARγ agonist (Alibin et (Tsai et al, 2009). Moreover, Thiazolidinedione (TZD), a well-known PPARγ agonist, also promotes TR4 activity in the reporter gene assay (Xie et al, 2009). These previous reports strongly suggest that TR4 may function as a fatty acid sensor to modulate lipid homeostasis of our body (Xie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Thiazolidinedione (TZD), a well-known PPARγ agonist, also promotes TR4 activity in the reporter gene assay (Xie et al, 2009). These previous reports strongly suggest that TR4 may function as a fatty acid sensor to modulate lipid homeostasis of our body (Xie et al, 2009). Thus, we hypothesized that CLA, a dietary component of milk products and ruminant meats, may participate in lipid homeostasis in adipocytes in part by modulation of TR4 activity.…”
Section: Introductionmentioning
confidence: 99%